2009
DOI: 10.1111/j.1745-3933.2009.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a short orbital period in the Supergiant Fast X-ray Transient IGR J16479–4514

Abstract: We report here the discovery of a 3.32 d orbital period in the Supergiant Fast X‐ray Transient (SFXT) source IGR J16479−4514. Using the long‐term light curve of this source obtained with Swift Burst Alert Telescope (BAT) in the energy range of 15–50 keV, we have clearly detected an orbital modulation including a full eclipse of duration ∼0.6 d. In the hard X‐ray band of the BAT instrument, the eclipse ingress and egress are rapid. We have also used the long‐term light curve obtained with the Rossi X‐ray Timing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 49 publications
4
57
0
Order By: Relevance
“…Some authors have suggested that the eclipse by the SG star causes the X-ray dark phase in this system (Bozzo et al 2008b). Since this system shows marginal properties between the classical OB-type HMXB and an SFXT, it could be a prototype system that bridges new and classical understandings of HMXBs (Sguera et al 2008;Jain et al 2009). Further observations and discussions on this source are strongly required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have suggested that the eclipse by the SG star causes the X-ray dark phase in this system (Bozzo et al 2008b). Since this system shows marginal properties between the classical OB-type HMXB and an SFXT, it could be a prototype system that bridges new and classical understandings of HMXBs (Sguera et al 2008;Jain et al 2009). Further observations and discussions on this source are strongly required.…”
Section: Discussionmentioning
confidence: 99%
“…In the list of observed SFXTs (Table 1), IGR J16479-4514 has an extremely short orbital period, P orb = 3.2 d (Jain et al 2009). Although it is suggested that this system has a large eccentricity, such a system with short orbital period likely becomes a persistent source or contact binary, according to our result (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this class of systems can be an accretor with retrograde accretion. In addition, IGR J16479-4514, with P s = 2.14 s (http://hera.ph1.uni-koeln.de/~heintzma/ Integral/SFXT.htm) and P orb = 3.3 days (Jain et al 2009), also present a somewhat larger corotation radius. Therefore, it can also behave like an retrograde accretor.…”
Section: Application To Sfxtsmentioning
confidence: 99%
“…de/~heintzma/Integral/SFXT.htm, P orb = 18 days, Jain et al 2009; for IGR J17544-2619, P s = 71.49 s, Drave et al 2012, P orb = 4.9 days, Clark et al 2010. From the expressions of r mag and r cor (see Eqs.…”
Section: Application To Sfxtsmentioning
confidence: 99%